Coxsackievirus B5 virus-like particle vaccine exhibits greater immunogenicity and immunoprotection than its inactivated counterpart in mice. Issue 39 (15th September 2021) - Zhang, Ning; Zheng, Tianpeng; Chen, Yongbei; Zhu, Hanyu; Qu, Ying; Zheng, Huanying; Liu, Hongbo; Liu, Qiliang
Highlights: A CVB5 VLPs vaccine was constructed by an insect baculovirus expression system. The CVB5 VLPs vaccine showed stronger immunogenicity than inactivated CVB5 vaccine. Abstract: Coxsackievirus B group 5 (CVB5) represents one of the major pathogens that cause diseases such as hand, foot and mouth disease (HFMD) and aseptic meningitis et al. Currently, no specific drugs and vaccines are available, and a safe and effective CVB5 vaccine is of great value for control of the diseases. In this study, CVB5 P1 precursor and 3CD protease were co-expressed in Sf9 cells by using a baculovirus expression system. The P1 was processed by 3CD and self-assembled into CVB5 virus-like particles (VLPs). VP1 and VP3 capsid proteins of CVB5 could be detected by SDS-PAGE and Western blotting. Transmission electron microscopy revealed that the CVB5 VLPs were spherical particles with a diameter of about 30 nm, mimicking wild-type CVB5 virus. Our study showed that the total IgG and neutralizing antibodies induced by CVB5 VLPs were higher than those induced by inactivated vaccine. More importantly, the CVB5 VLPs conferred full protection to the CVB5-challenged suckling mice via passive immunity while protection efficiency of the inactivated vaccine was only 80%. The CVB5 VLPs vaccine could protect the limb muscles, brain, and heart tissues of suckling mice from CVB5-induced damage. These results demonstrated that the CVB5 VLPs vaccine possessed stronger immunogenicity and provided more robust immunoprotection than the inactivated CVB5 vaccine, suggesting that the CVB5 VLPs promise to be a CVB5 vaccine candidate in future.